INTEGRATIVE MATHEMATICS LEARNING: STUDY OF HADITHS ON NUMBER - Novita Erni Hendrawati; Suci Wulandari; Moh. Miftakhul Ulum; Muhammad Hasan Asnawi; Imam Rofiki; Abdussakir Abdussakir (Abjadia, 2020)
Integrative mathematics learning is needed in the study of science and religion, especially in the madrassa and the Islamic University, to improve morality for all students in Indonesia. This study aims to examine the hadith regarding integers and integer operations in integrative mathematics learning. Mathematical learning is expected to increase students' religious knowledge and mathematical knowledge. The method used in this research is literature study. In the hadith, some integers are 1,2,3,4,5,6,7,8,9,10 and integer operations, namely addition, subtraction, multiplication, and division. The hadiths related to numbers and number operations are HR. Bukhari 40; 71; 15; 33; 1334; 1761; 1109, HR. Muslim 19; 1984; 1513; 1991, HR. Darmini 3174, HR. Ibnu Khuzaimah 301, and HR. Tirmidhi 565.